Development of Response-to-Intervention model-based Program & Evaluating its Effectiveness on Spelling Improvement - زهرا امین ابادی; حمید علیزاده; اسماعیل سعدی پور; صغرا ابراهیمی قوام; نورعلی فرخی (Ravānshināsī-i Afrād-i Istis̠nāyī, 2016)
This study aimed to develop a Response-to-Intervention (RtI) program in order to enhance spelling skill and to examine its effectiveness for third-grade students with spelling problems. The study was conducted in two stages including program development and utilizing evaluation a single-system design (AB). The study population consisted of third-grade students from the city of Karaj in the school year of 2015-216. Twenty students were selected as the sample using targeted sampling method. These students were incorporated in a three-tiered intervention based on response-to-intervention model (first tier included groups of five in nine 30-minute sessions, second tier consisting of groups of three in nine 45-minute sessions and the third tier including 12 individual one-hour sessions) and were trained for the developed program which was tailored for response-to-intervention model using direct instruction method. Measuring tools were the spelling test of Rezaei & Karimi (2013). According to the results of ICC, the developed program’s validity is 0.36, which is a good validity for implementation considering that P